PENERAPAN PEER TEACHING UNTUK MENINGKATKAN HASIL BELAJAR LAY UP PERMAINAN BOLA BASKET DI KELAS 3.2.5 SMP NEGERI 3 MALANG - Shintia Eka Arfenda; Usman Wahyudi; Shintia Eka Arfenda (Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan, 2024)
The purpose of this research is for students to obtain better learning outcomes. To overcome these problems, researchers use students who have better abilities from his friend to serve as a model or peer tutor. FigureThese peer tutors are students have more capabilities well and work to help the task one person teachers in guiding and training his friends especially on the subject matter shoot (lay up shoot). The research method using collaborative classroom action research (PTKK) is divided intoII continuous cycle with subject research by class 3.2.5 students of SMP Negeri 3 Malang. The result is that students show thorough learning about general information in the second cycle I learning session from 71% to 87%, in the second cycle II meeting. Conclude that the application of the peer tutoring method has succeeded in improving the learning process and encouraging increased student academic achievement.